2016
DOI: 10.1088/0964-1726/25/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Study of pseudoelastic systems for the design of complex passive dampers: static analysis and modeling

Abstract: This work presents an experimental and numerical analysis of several parallel systems of NiTi pseudoelastic wires. Standard tensile tests were accomplished to evaluate the global damping capacity, the energy dissipated per cycle and the maximum attenuated force in a static condition. Besides, a numerical model was implemented to predict the damping response of more complex pseudoelastic arrangements. It was found a damping capacity upper limit of 0.09 regardless the number and the length of the NiTi components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Quasi-static and dynamic cyclic tests have been performed by Nespoli et al [13,14] to assess the mechanical behavior, initially on single SMA wires, subsequently on pseudoelastic systems (composed by groups of two wires), and finally on the global device ( Fig. 1(b)).…”
Section: Shape-memory Alloy (Sma) Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Quasi-static and dynamic cyclic tests have been performed by Nespoli et al [13,14] to assess the mechanical behavior, initially on single SMA wires, subsequently on pseudoelastic systems (composed by groups of two wires), and finally on the global device ( Fig. 1(b)).…”
Section: Shape-memory Alloy (Sma) Devicementioning
confidence: 99%
“…Therefore, the work is organized as follows: in Section 2 we discuss the novel passive damper developed by Nespoli et al [13], composed by a parallel system of shape-memory alloy wires (indicated as 'SMA device'). Initially, we focus on the device dynamics, both empirically (through experimental tests performed by Nespoli et al [14]) and numerically (by means of 3D finite element models developed using the software Abaqus [15], in Section 2.1).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, NiTi components are used to preserve instrumentations and sensitive equipment from environmental noise and structural vibrations. [ 2–8 ] The practical applications of NiTi dampers are usually under isothermal conditions and may involve either low or high strain amplitudes, encouraging two different methodologies of investigation, accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Proper thermo‐mechanical processing and NiTi composition can maximize the transformation hysteresis, inducing high loading and low unloading plateau. [ 7 ] Pseudoelastic NiTi is now deeply studied for those applications that involve large parts or assemblies such as buildings [ 14,15 ] and space structures, [ 16–20 ] thanks to both the large superelastic strains (up to 8%) and the self‐centering capability.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in construction methods and materials have led to more flexible structures, thereby raising the demand on reducing vibrations caused by natural hazards. Such vibrations can be mitigated through the incorporation of supplemental damping devices, including passive [1,2], semi-active [3,4,5] and active [6,7] systems. Of interest to this paper are passive systems, which have been widely accepted by the field due to their mechanical robustness and mitigation performance without necessitating external power [8].…”
Section: Introductionmentioning
confidence: 99%